(untitled) (The Scientific Journal of University of Saba Region, 2025)
This paper examines how the structure of A Passage to India is used as a framework to convey the stereotype of the “Other” as inferior and as a tool for political propaganda, reflecting Forster’s colonial views. While many scholars have studied Forster’s political ideas in the story, they have not focused on how the structure of the narrative has been carefully employed by the author to convey these negative political views. Using Greimas’ framework of actants-subject, object, sender, receiver, helper, and opponent, this paper examines key interactions, such as those between Mrs. Moore, Adela, and Dr. Aziz at the mosque, the Bridge Party, and the Marabar caves, and how that such encounters are used to mock the newcomer desire see real India- the object of their interest. After these four encounters, the women ultimately abandon their hope to see real India mirroring the truthfulness of negative experience of the English who advise them to keep away from the Indians if they want to be safe.